Comparative Analysis of Drilling Behaviour of Synthetic and Natural Fiber-Based Composites - A. Mohan Kumar; R. Rajasekar; P. Manoj Kumar; R. Parameshwaran; Alagar Karthick; M. Muhibbullah (Advances in Materials Science and Engineering)
For comparison, the drilling behaviour of abaca fiber-reinforced polymer (AFRP) composites and Kevlar-reinforced epoxy polymer (KFRP) composites has been studied in the specified experimental condition. The different geometrical drilling tools have been used for the investigation, namely, candlestick (T1), core (T2), standard twist drill (T3), and step cone (T4). The tool feed of 30, 45, and 60 m/min and rotational speed of 1000, 1500, and 2000 rpm have been used for the investigation. The thrust force is chosen as a response parameter for this study. The results revealed that, at lesser rotational speed and tool feed, the thrust force has declined. The result obtained correlates with the abaca fiber-based systems. However, the thrust force of KFRP is higher compared to AFRP composite systems. The axial force generated by candlestick drill is minimal compared to the other drill bits. The following may be responsible for lower thrust force: (1) the axial force distributes circumferential of the cutting tool instead of focusing at the center and (2) the interfacial adhesiveness between the matrix and the fiber is higher. The optimization of drilling process parameters, namely, tool feed and rotational speed on thrust force, has been studied. The results reveal that the tool feed contributed more to axial force compared to rotational speed.